Effects of sleep hygiene education and lavender oil inhalation on sleep quality, fatigue, and health-related quality of life in adults with an ostomy: a randomized controlled trial protocol - Koca, Rabia; Gurkan, Aysel; Fehmi Küçük, Hasan (International Journal of Clinical Trials, 2023)
Background: It has been shown that the formation of an ostomy affects sleep quality, and sleep problems or insomnia cause fatigue in daily life, reducing the health-related quality of life. This trial aims to investigate the effects of sleep hygiene education and lavender oil inhalation alone and in combination on sleep quality, fatigue, and health-related quality of life in adults with an ostomy. Methods: This trial has been planned as a randomized controlled clinical trial and will use a 2×2 factor design in which an equal number of participants meeting the inclusion criteria will be randomly allocated to one of four groups. The study sample will comprise 120 adult patients who have undergone ostomy surgery in a city hospital in Turkey. Lavender oil inhalation together with sleep hygiene education will be applied in the first group (n=30), only sleep hygiene education in the second group (n=30), only lavender oil inhalation in the third group (n=30), and no intervention in the fourth group (n=30). The sleep quality of the groups will be evaluated using the Pittsburgh sleep quality index, their fatigue levels with the chalder fatigue scale, and their quality of life with the ostomy a quality-of-life scale. Conclusions: Non-pharmacological interventions are needed to prevent sleep and/or other problems that may develop due to insomnia in adults with ostomy. By evaluating the effects of these interventions, this trial will provide valuable evidence to guide clinical practice. Trial registration: This trial was registered in October 2022 (NCT05573256).